Closing the Achievement Gap: An Analysis of Equity-Based Educational Interventions - Haxhiu, Zairika (Journal of Education Review Provision, 2022)
This research focus on examining effects of equity-based educational practices on closing an achievement gap with main emphasis placed on underprivileged students. The approach the research employed is the quantitative and qualitative research where findings include the pre and post-intervention, test scores, engagement levels, and attendance where it is complemented by interviews and focus group discussions. These are evidenced in the areas of academic achievement, student attitude and behavior, and social emotional learning with emphasis made on the lowest SES students However, they also noted limitations and threats inherent with the change process such as: resistance to change; scarcity of resources; and unsure future of the said interventions. Based on the findings from the study, the author opines that equity based interventions are useful in promoting equity in education delivery however they require enhancement of support, sufficient resource mobilization and enhanced community participation. The findings provide significant insights into how educators and policy makers can strengthen preservice teachers abilities to support equity- oriented reform efforts in K-12 classrooms as well as promote and maintain such reforms. Thus it is recommended that future research focus on the sustained impact of these interventions and strategies with regards to the hurdles encountered in the process of implementation.